Problem-Solving Skills on Night Sky Brightness and Light Pollution: A Rasch Analysis - Silvia Lutfiani; Winny Liliawati; Ahmad Aminudin (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
Instruments for measuring problem-solving skills in physics education have primarily been developed in the context of classical physics. In contrast, the astronomy context, based on real phenomena, has remained relatively limited. One phenomenon closely related but not widely utilized as an assessment context was night sky brightness as an indicator of light pollution. Therefore, this study aimed to examine the feasibility of problem-solving skill instruments in the context of night sky brightness as an indicator of light pollution, as well as to describe physics education problem-solving skills. This study employed a quantitative descriptive design involving 75 students in physics education. The instrument was designed in the form of a contextual problem, covering four problem-solving stages and was analyzed using the Rasch Model. The analysis results indicated that the instrument met the feasibility criteria for use as a measurement tool for problem-solving skills. The use of this instrument provided an overview of students’ abilities at each problem-solving stage, so that the assessment did not focus solely on the final score but also on students’ thinking processes. Thus, this study contributed to the development of an astronomy-based assessment instrument that could be used as a diagnostic tool for problem-solving skills in physics learning.